Exploring emotion dysregulation in adolescence and its association with social immaturity, self-representation, and thought process problems - Cristofanelli, Stefania; Testa, Silvia; Centonze, Eleonora; Baccini, Giorgia; Toniolo, Federico; Vavalle, Vincenza; Ferro, Laura (Frontiers in Psychology, 2024)
This study aimed to explore the complex phenomenon of emotional dysregulation, particularly in adolescence, which is associated with many mental health disorders and problems. Increasing the knowledge of clinicians and researchers in this area can be helpful in guiding future treatment plans. The aim of the study was to investigate, in an exploratory perspective, which structural aspects of adolescent functioning (assessed using the Rorschach test, administered and scored according to the Comprehensive System, CS, by Exner) were associated with different dimensions of emotional dysregulation (evaluated using the Difficulties in Emotion Dysregulation Scale, DERS). Method: Secondary data were used for the study, including 100 adolescents, with 50 in the clinical group (patients with complex trauma histories residing in therapeutic and sociorehabilitative communities) and 50 in the non-clinical group (recruited from a scout group and middle and high schools). The two groups were compared in terms of the means of scores obtained in the DERS scales (one-tailed t-test) and the proportions of cases that obtained pathological values in selected Rorschach CS indicators (z-test). The first comparison confirmed that the clinical group had higher levels of emotional dysregulation, while the second comparison identified the Rorschach CS variables that discriminated between the two groups. Partial correlations were calculated between the DERS scales and the Rorschach CS variables to explore which structural dimensions of functioning were associated with different characteristics of emotional dysregulation. Results: The results indicated that the two groups differed in their outcomes in all DERS scales, except for Awareness and Goals, and in four Rorschach CS variables (EgoIndex, a:p, Wsum6, and MOR). Some significant positive and negative correlations between the Rorschach CS variables and the DERS scales also emerged. Conclusions: These results suggested that the functioning dimensions associated with emotional dysregulation and related to self-representation, relational immaturity, and thought processes characterized membership in a therapeutic community. The analysis of the correlations described in the article entitled further considerations. Finally, study's limitations and future research prospects were presented.